"Razparač iz Rojana" - Jović, Bojana (Kronika (Ljubljana), 2016)
"The ripper of Roiano". The case of Julius Födransperg of 1908 in light of press coverage. The paper describes the infamous murder case of Julius von Födransperg. The events are set in 1908, when a Trieste fisherman hauled from the sea a parcel containing a severed human head. The discovery created a hugesensation that made headlines everywhere. Before long, the investigation identified Julius Födransperg as the murderer, drawing even more attention to the case. To staisfy the readers' curiosity, the press began to dig through Födransperg's past, which turned out to be anything but an example of noble living. Little wonder, then, that Trieste "ripper" received press coverage not only in Trieste, Ljubljana and Vienna, but also in the American press.
Keywords: 1908; biografije; časopisje; Födransperg, Julij; Kazniva dejanja; morilci; Trst; Umori